Intensified Population Exposure Risks of Compound Heatwaves Over Sichuan–Chongqing: The Role of Anomalous Tibetan Plateau Heat Source - Huning Chen; Fei Ge; Zhang Chen; Quanliang Chen (International Journal of Climatology, 2026)
Compared with heatwaves that occur only at daytime or nighttime, daytime‐nighttime compound heatwaves (CHWs) cause more severe damage to natural ecosystems and human society. This study aims to investigate the relationship between the frequency of compound heatwaves (CHWF) in the Sichuan–Chongqing (SC) region and the atmospheric apparent heat source (AHS) over the southeastern Tibetan Plateau (TP) during 1985–2014. Furthermore, future changes in this relationship and population exposure to CHWs associated with anomalous AHS are examined using simulations from the Coupled Model Intercomparison Project 6 (CMIP6). Results show that this relationship is projected to strengthen significantly during 2071–2100 under the SSP2‐4.5 and SSP5‐8.5 scenarios, with a larger enhancement in the AHS–CHWs linkage under higher emissions, likely associated with amplified interannual variability of the AHS. However, population exposure to CHWs associated with anomalous AHS in the SC region is projected to increase 2.83‐fold and 2.72‐fold for SSP2‐4.5 and SSP5‐8.5, respectively. Exposure risk levels in eastern SC are also projected to increase by the end of this century, with ultra‐high risk zones emerging and covering 1% (2%) of the area, affecting 11% (17%) of the population, under the SSP2‐4.5 (SSP5‐8.5) scenario. This study highlights the escalating threats of AHS‐related CHWs over the SC region in a warmer future, further underscoring the importance and urgency of implementing emission reduction commitments and climate adaptation strategies.

The regulatory role of miR-21 in ferroptosis by targeting FTH1 and the contribution of microglia-derived miR-21 in exosomes to arsenic-induced neuronal ferroptosis - Huanhuan Wang; Xudan Liu; Yao Chen; Wanying Li; Yanhong Ge; Huning Liang; Bin Xu; Xin Li (Journal of Hazardous Materials, 2024)

Arsenic induced autophagy-dependent apoptosis in hippocampal neurons via AMPK/mTOR signaling pathway - Yao Chen; Xudan Liu; Qianhui Zhang; Huanhuan Wang; Ruo Zhang; Yanhong Ge; Huning Liang; Wanying Li; Juanjun Fan; Huimin Liu; Zhengyang Lv; Wenting Dou; et al. (Food and Chemical Toxicology, 2023)